Beobachtungen über die Entstehung von Buckelweiden auf den Hochflächen des Schweizer Jura - Schreiber, Karl-Friedrich (ERDKUNDE, 1996)
On some high pastures of the Swiss Jura, areas with a more or less dense cover of earth hummocks can be observed, whose appearance is reminiscent of the variously-described 'Thufur' fields of Iceland and similar forms, caused by frost-heaving. In reality, however, these earth hummocks are built by the yellow field ant Lasius flavus F. Indeed, the formation of these earthen domes, found only in relatively fresh grass depressions, is linked to an extensive pasture use and is especially favoured by a fertilising practice, the so-called 'Gfählen', which was formerly widely practised in the Swiss Jura. Young queen ants, after the wedding flight in high summer, like to embed themselves in the ground underneath cow-dung cakes either naturally deposited or brought into the field in the 'Gfählen'. In the following spring the first eggs are laid. The worker ants, when hatched, industriously begin to build an earth hill on one side of the gradually decaying cow-cake. This rather 'powerful' area, despite its relatively luxuriant vegetation cover, is not eaten by animals and also not trod upon! The earth hill is built ever higher in constant competition with the grasses which threaten to cast it into shadow. In the following years, on the grounds of climatic favour and warmth, the battle area is shifted ever more to the south east side of the construction as, in the high pasture, this is evidently the only place where the preconditions for breeding and rearing are satisfied. At the same time, a eutrophic situation develops from the very active life in this zone which permits strong growth of particular early dominant grass types, especially, for example, Agrostis tenuis. As far as one can see, a growth stimulating process is also caused by the saliva of the root lice which are used by the ants for the symbiotic derivation of honeydew. In any case, the field ants are forced to counter the over shadowing effect of the rapidly growing blades of grass by continually heaping earth on them. In this way, the ants nest gradually takes on a south-easterly orientation, typical of all the older hummocks on the high pastures. Given extensive pasture use and little outside intervention, such a 'hummocked field' can develop its main characteristics in a period of 10 to 15 years.